KEPADATAN POPULASI ULAT PENGGEREK TONGKOL (Helicoperva armigera Hubner) PADA TANAMAN JAGUNG DI KELURUHAN PISANG KECAMATAN PAUH PADANG - Vera, andika putri; Jasmi, Jasmi; safitri, Elza (Pendidikan Biologi, 2014)
ABSTRACTÂ One of harmful on maize cob borer is a caterpillar (Helicoperva armigera Hubner). Caterpillar attack the corn up to grain filling stadia on the cob. These caterpillars attack corn plants by way of invading entered in to the cob and ate the seeds in the cob. Symptoms of attacked plants characterized by hair cut of corn cobs, cobs end there is a used hoist and often times there are larvae. These caterpillars can reduce the quality and quantity of corn. This study aims to determine the population density of borer caterpillars on corn cobs In the Keluruhan Pisang Kecamatan Pauh Padang. Physical factor measured by temperature and humidity. This type of research is survey descriptif. The study started from September-oktober 2013 di Keluruhan Pisang Kecamatan Pauh Padang. Field sampling was conducted on maize plants age of 50 days and 70 days after planting. Field samples is done by dividing the total area of 20x20 m corn plants into five parts, namely the edges and the middle of the size of 3x3 m. Furthermore, samples collected in 3x3 m plots with units per stick in a random way. The results were obtained borer caterpillar population density on corn cobs age of 50 days after Planting more densely is 252 individuals/plant with an average of2,02 at the age of 70 corn crop Â that is 124 days after Planting individuals/plant with an average of0,99. Cob borer caterpillar densities found are included pests.Â